Concomitant intra-atrial excision of the left atrial appendage during robotic-assisted minimally invasive cardiac surgery - Ghinescu, Mihnea; Franke, Ulrich F. W.; Ortega, Melisa; Hüther, Franziska; Rufa, Magdalena I.; Göbel, Nora (Frontiers in Cardiovascular Medicine, 2023)
Objective: Surgical closure of the left atrial appendage (LAA) in patients with atrial fibrillation undergoing cardiac surgery can decrease the risk of stroke and thromboembolism and should therefore be considered. In minimally invasive, thoracoscopic, or robotic-assisted mitral valve surgery, however, external procedures such as clip application or epicardial resection are not feasible due to anatomic limitations and the reduced size of the access port. Internal suture closing techniques bear the risk of recurrent LAA reperfusion, so far. We present a novel surgical technique of LAA excision and subsequent defect closure from the interior aspect of the atrium. Methods: We developed this novel technique during robotic-assisted cardiac surgeries. In short, the LAA is invaginated into the left atrium, excised completely at the base using scissors and the stump is then closed from the inside with a two-layer looped PTFE suture. We give a detailed step-by-step description of the technique. Results: A total of 20 patients received intra-atrial LAA excision so far. Complete resection of the LAA without any residual stump or bleeding was achieved in all cases. There were no procedure-related complications. Conclusion: The intra-atrial LAA excision technique shows promising preliminary results regarding efficacy, safety, and reproducibility during robotic-assisted cardiac operations and could be recommended for all right-sided minimally invasive cardiac surgical procedures.